PERSPEKTIF FEMINIS DALAM NOVEL PEREMPUAN DI TITIK NOL TERJEMAH NOVEL IMRA’ATUN’INDA NUQTAH AL-SHIFR KARYA NAWAL EL-SA’DAWI DAN PEREMPUAN BERKALUNG SORBAN KARYA ABIDAH EL-KHALIEQY - Ambarwati, Amiroh (IAIN Pekalongan, 2009)
In the patriarchy society, women are viewed to be the second class depending on men. Culture and custom demand women to be under men. It makes women stand in the back side an oppression. In contrast, man were supposed to be the first class, who dominating. The research aims at investigating the existence of women in Nawal El-Sa’adawi’s Perempuan di Titik Nol and Abidah El-Khalieqy’s Perempuan Berkalung Sorban to realize the existence to be human being having value and prestige appropriated with her potentions.